Kajian penerapan Sistem Manajemen Keselamatan Konstruksi (SMKK) Studi kasus pelaksanaan pembangunan jalan dan Jembatan Kemiri-Depapre (MYC) Kabupaten Jayapura Provinsi Papua - Paturusi, Muhammad Yaslan; Supardi, Sudarman; Watono, Watono (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to evaluate the implementation of the Construction Safety Management System (SMKK) on the Kemiri-Depapre (MYC) Road and Bridge Construction Project in Jayapura Regency, Papua Province. The research results show that the implementation of SMKK in this project has generally gone well and is in accordance with statutory regulations, namely PUPR Ministerial Decree No. 10 of 2021. Internal audit carried out at PT. Brahmakerta Adiwira as the construction implementer demonstrated compliance with safety, health and security standards. Independent variables such as awareness of the importance of K3, K3 training, and K3 supervision have a significant contribution to the level of implementation of SMKK and the frequency of work accidents. Based on the Adjusted R-Square value, simultaneously the influence of the independent variable on the dependent variable varies between 46.60% to 96.30%. Individually, 83.33% of independent variables have a significant effect on the number of work accidents, 5.56% have a significant effect on project efficiency and productivity, 44.44% have a significant effect on the quality of implementation and work results, and 55.56% have a significant effect on the level of worker satisfaction with the implemented safety program. Implementing a good SMKK not only guarantees safety for workers but also provides economic benefits, maintains the image of the organization, and increases productivity and quality of construction work. It is hoped that this research can become a reference for construction industry players in increasing the implementation of K3 on their projects..